Strengthening Climate Resilience Through Urban Policy: A Mixed-Method Framework with Case Study Insights - Shiyao Zhu; Haibo Feng (Land)
While climate resilience is a growing priority in urban planning, limited attention has been given to the procedural and governance mechanisms needed to effectively integrate resilience into policy development. This study presents a comprehensive policy analysis aimed at enhancing climate resilience, using the city of Kamloops, Canada, as a case study. A policy evaluation framework was developed, encompassing four dimensions and 20 indicators, to assess 11 policies and bylaws in Kamloops. The evaluation yielded a moderate score of 0.559 out of 1, revealing both existing strengths and critical gaps in the city’s climate resilience strategies. Key challenges identified include policy inflexibility, the absence of clear climate adaptation goals, insufficient emphasis on education and research, the lack of long-term projections and risk assessments, and implementation gaps such as unclear timelines, responsibilities, and funding mechanisms. To validate these findings, interviews with city staff from multiple departments provided further insights into governance barriers and opportunities for policy enhancement. Beyond Kamloops, this study offers a scalable and adaptable framework for cities worldwide seeking to integrate resilience into their urban planning policies. By addressing governance and procedural challenges, cities can strengthen their capacity to mitigate climate risks, enhance sustainability, and build long-term urban resilience.